Comparison of correlation between protein and iron intake with hemoglobin levels in children age 6-23 and 24-36 months during COVID-19 pandemic in east Jakarta - Stella Kristi Triastari; Saptawati Bardosono; Dian Novita Chandra (Indonesian Nutrition Association, 2022)
Background and objectives : Anemia prevalence, especially iron deficiency anemia, among Indonesian toddlers is high. Iron deficiency may interfere nerve development and also cause immune problems. Protein malnutrition may also cause anemia. The prevalence is higher in 6-23 months age group due to the increase need. However, the correlations between iron and protein intake with hemoglobin levels are still showing different results and researches don’t compare the correlation between age groups.